2013
DOI: 10.1589/jpts.25.1343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bridging Exercise on Different Support Surfaces on the Transverse Abdominis

Abstract: [Purpose] The purpose of this study was to identify the effects of bridging exercise on different support surfaces on the thickness of the musculus transversus abdominis and lower extremity muscle activities. [Subjects] Thirty-five students of H University. [Methods] The experimental group (n=18) performed bridging exercise on the sling support surface, and the control group (n=17) performed bridging exercise on a general support surface. [Results] Thickness changes in the musculus transversus abdominis were 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…In particular, sensorimotor training on an unstable supporter lead-ing to redistribution of muscles tone, activation of balance coordination, and increasing the sensory feedback via counterbalancing among both nervous and muscles system. Consequently, balance is restored through enhancement of the feed-back response of the motor system, co-contraction levels, and joint stability [4] [20]. In this regard, various reports revealed that, sensorimotor training on an unstable surface drove the activation of various co-contracted muscles such as deltoid, triceps, and spine muscles.…”
Section: Balance and Sensorimotor Trainingmentioning
confidence: 99%
“…In particular, sensorimotor training on an unstable supporter lead-ing to redistribution of muscles tone, activation of balance coordination, and increasing the sensory feedback via counterbalancing among both nervous and muscles system. Consequently, balance is restored through enhancement of the feed-back response of the motor system, co-contraction levels, and joint stability [4] [20]. In this regard, various reports revealed that, sensorimotor training on an unstable surface drove the activation of various co-contracted muscles such as deltoid, triceps, and spine muscles.…”
Section: Balance and Sensorimotor Trainingmentioning
confidence: 99%
“…However, Lister et al 20 ) reported that FB for shoulder-stabilizing exercises increased scapular activity more than that with general resistance devices. Concurrently, Eom et al 21 ) argued that exercises that provide dynamic environments increase myotility due to increases in myofibrils that engage in motor control. Additionally in rehabilitation programs for patients with shoulder pathology, the importance of muscle strengthening of the trapezius and the SA, which are scapular upward rotators, is further emphasized 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving 51 patients with chronic low back pain, Saliba et al 11 ) demonstrated that bridge exercises on an unstable support surface provided by slings were more effective at increasing TrA muscle activity than bridge exercises on stable bearing surfaces as measured by ultrasonography. Eom et al 12 ) reported that bridging exercises performed by healthy persons using slings as an unstable support surface showed larger increases in TrA thicknesses than bridging exercises performed by the same persons on stable bearing surfaces. In a study conducted by Brumagne et al 13 ) with chronic low back pain patients, in which proprioceptive sense exercises and local vibrations were additionally applied, proprioceptive stimuli and deep muscle control abilities of the subjects improved.…”
Section: Discussionmentioning
confidence: 99%